Is the double‐guidewire technique superior to the pancreatic duct guidewire technique in cases of pancreatic duct opacification?. Issue 11 (22nd October 2013) - Tanaka, Reina; Itoi, Takao; Sofuni, Atsushi; Itokawa, Fumihide; Kurihara, Toshio; Tsuchiya, Takayoshi; Tsuji, Shujiro; Ishii, Kentaro; Ikeuchi, Nobuhito; Umeda, Junko; Tonozuka, Ryosuke; Honjo, Mitsuyoshi; et al.
Abstract: Background and Aims: Pancreatic duct guidewire placement (P‐GW) techniques include both the injection cannulation technique with a contrast medium and wire‐guided cannulation without contrast injection for selective biliary cannulation; the latter is the so‐called "double‐guidewire technique" (D‐GW). The aim of this study was to compare the outcomes between P‐GW and D‐GW for biliary cannulation. Methods: The procedures for biliary cannulation with a naïve papilla were performed in a total of 363 cases. We divided the patients chronologically, according to the time period during which the procedures were performed, into two groups: group A, P‐GW performed from March 2008 to June 2009; and group B, D‐GW performed from July 2009 to December 2010. The success rates and complication rates were evaluated in each group. Results: Biliary cannulation was successful in 31 (81.6%) patients in the P‐GW group and 34 patients (82.9%) in the D‐GW group. The onsets of postendoscopic retrograde cholangiopancreatography pancreatitis (PEP) occurred in the P‐GW and D‐GW groups were four (10.5%) and three (7.3%) patients, respectively, and all were mild cases ( P  = 0.616). The frequency of hyperamylasemia and the serum amylase level tended to be lower in the D‐GW group than in the P‐GW group ( P  = 0.213). There was a statistically significant difference on the onsets of PEP in the GW and non‐GW groups ( P  = 0.04, 8.9% and 1.1%, respectively). Conclusions: Both the D‐GW and P‐GW techniques were equally effective for difficult biliary cannulation. Furthermore, the complication rates, including PEP, were similar in both techniques. A prospective randomized trial is warranted.